Basic Swimming Style Crawl Engineering Skills Survey in Athletes Ages 10-12 - Puput Widodo; Fatma Zainul Yunida (JUMORA: Jurnal Moderasi Olahraga, 2021)
This study aims to: 1.To know the basic technique skills of crawl style swimming in the Kebumen swimming club association students. 2. Knowing the factors of difficulty experienced by students in learning the basic motion skills of crawl style swimming 3. Students are able to apply the basic movements of swimming with the right steps. This research was conducted on the students of the Kebumen swimming club association in Gossi Kebumen. The research plan is carried out in November 2021. The sample referred to in this study is 20 students in the 10-12 year age group who take part in basic swimming skills training. Descriptive data analysis was entered to get an overview of the data including the average, standard deviation, maximum data, minimum data, range, frequency table and graphs. Based on the results of the research that has been carried out, it can be concluded: 1. Freestyle swimming skills measured using a stopwatch on students aged 10-12 years at the swimming club association in Kebumen showed that 50% of students had very poor swimming skills, 25% students have poor swimming skills and 25% of students have sufficient skills. 2. The category of skills that dominates the most in students is very low ability. Contributing to further research is to conduct research on more intense exercises on crawl swimming style techniques need to be done by athletes and also strategies to improve the ability of athletes in crawl style swimming.Keywords: Swimming, Crawl Style, Basic Swimming Technique